LO50: Pain free laceration repairs using intra-nasal ketamine: DosINK 2 clinical trial. (May 2020) - Rached-Dastous, S.; Trottier, E. D.; Finkelstein, Y.; Bailey, B.; Marquis, C.; Lebel, D.; Desjardins, M.
Abstract : Introduction: Lacerations are common in children presenting to the emergency department (ED). They are often uncooperative when sutures are needed and may require procedural sedation. Few studies have evaluated intranasal (IN) ketamine for procedural sedation in children, with doses from 3 to 9 mg/kg used mostly for dental procedures. In a previous dose escalation trial, DosINK-1, 6 mg/kg was found to be the optimal IN ketamine dose for procedural sedation for sutures in children. In this trial, we aim to further evaluate the efficacy of this dose. Methods: We conducted a multicentre single-arm clinical trial. A convenience sample of 30 uncooperative children between 1 and 12 years (10 to 30 kg) with no cardiac or kidney disease, active respiratory infection, prior administration of opioid or sedative agents received 6 mg/kg of IN ketamine using an atomizer for their laceration repair with sutures in the ED. The primary outcome was defined as the proportion (95% CI) of patients who achieved an adequate procedural sedation evaluated with the PERC/PECARN consensus criteria. Results: Thirty patients were recruited from April 2018 to November 2019 in 2 pediatric ED. The median age was 3.2 (interquartile range(IQR), 1.9 to 4.7) years-old with laceration of more than 2 cm in 20 (67%) patients and in the face in 21 (70%) cases. Sedation was effective in 18 out of 30 children 60% (95%CI, 45 to 80), was suboptimal in 6 patients (20%) with a procedure completed with minimal difficulties, and unsuccessful in the remaining 6 (20%), all without serious adverse event. Similarly, 21/30 (70%) physicians were willing to reuse IN ketamine at the same doses and 25 parents (83%) would agree to the same sedation in the future. Median time to return to baseline status was 58 min (IQR, 33 to 73). One patient desaturated during the procedure and required transitory oxygen and repositioning. After the procedure, 1 (3%) patient had headache, 1 (3%) patient had nausea, and 2 (7%) patients vomited. Conclusion: A single dose of 6 mg/kg of IN Ketamine for laceration repair with sutures in uncooperative children is safe and facilitated the procedure in 60% (95%CI, 45 to 80) of patients, was suboptimal in 20% and unsuccessful in 20% of patients. As seen with IV ketamine, an available additional dose of IN ketamine for some children if needed could potentially increase proportion of successful sedation. However, the safety and efficacy of repeated doses needs to be addressed.